2009
DOI: 10.1007/s11199-008-9577-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient–Provider Communication About Sexual Health: The Relationship with Gender, Age, Gender-Stereotypical Beliefs, and Perceptions of Communication Inappropriateness

Abstract: This investigation examined patient-provider communication about sexual health related to gender and age. Data were collected from 277 individuals, aged 18-60, via convenience and snowball sampling at a large university in southwestern United States. Results indicate women are more proactive about their sexual health than men and tested for STDs more frequently. Women, more than men, initiate discussions with their healthcare provider about sexual health matters and healthcare providers are more likely to init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In the general population, there is evidence that women are more likely than men to discuss sexual health concerns [148], and that absence of relationship communication on the part of male partners causes greater distress for women [149]. It has also been suggested that women’s wellbeing is more strongly associated with relational factors than men’s [150,151].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, there is evidence that women are more likely than men to discuss sexual health concerns [148], and that absence of relationship communication on the part of male partners causes greater distress for women [149]. It has also been suggested that women’s wellbeing is more strongly associated with relational factors than men’s [150,151].…”
Section: Discussionmentioning
confidence: 99%
“…For example, female general practitioners (GPs) use more affective behaviour (giving attention, reassurance) and male GPs use more instrumental behaviour (giving information) when communicating fatigue‐ or HIV‐specific information; the first strategy results in more effective or higher‐quality communication 12,14 . Male patients hold stronger gender‐stereotypical beliefs towards sexuality than female patients and are less likely to initiate conversations about sexual issues with their doctor 15 . Moreover, whether the doctor is a man or a woman has significant bearing when it comes to (non‐)dominating behaviour within the doctor–patient relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, there has been considerable interest in gender as a domain in doctor–patient communication education. Doctor competency frameworks and consensus statements on communication curricula have acknowledged and incorporated gender as a domain of clinical communication 2,3,12,15 . Recently, gender competencies have been determined for medical curricula (CanMEDS roles) to help educators to build and plan a competency framework that includes gender 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially recruited them by contacting people we knew had sought infertility treatment or who were referred to us by friends. We used snowball sampling to expand our informant pool-a technique found in many marketing studies, including those focusing on health care issues (e.g., Emmers-Sommer et al 2009). …”
Section: Context and Methodsmentioning
confidence: 99%